Efeitos da regulação no desempenho econômico-financeiro de organizações de saúde - Ewerton Alex Avelar (2018)
The research presented on this thesis aimed at analyzing the effects of the regulation of Unified Health System (SUS) and Agency of Supplementary Health (ANS) on the economic-financial performance of Brazilian health organizations (different categories of OPSs and voluntary hospitals) between 2010 and 2016. The study can be classified as a quantitative and explanatory one. It is based on secondary data gathered from government databases, which include voluntary hospitals and OPSs data. After collecting and treating the data, we applied the following data analysis techniques: descriptive statistics, Kruskal-Wallis’ test, Kolmogorov-Smirnov’ test, chi-squared statistics, Spearman’s coefficient correlation and panel data analysis. The financial ratios show the precarious management of voluntary organizations (both hospitals and OPSs). The analysis of the working capital management showed that most of the organizations present a good financial structure, expect in the case of the voluntary ones. It was possible to verify that all the regulatory variables related to financing decisions were significant to, at least, one category of OPS. On the other hand, only two regulatory variables related to financing decisions were significant in explaining the financing decisions in voluntary hospitals. Moreover, it is important to note that the variables significance change over the analyzed time (short term and long term). In analyzing the investment decisions (focusing on value creation), it was possible to observe that OPSs usually have aggregated more value than disaggregated (except the voluntary ones). One can say that the higher level of flexibility on ANS regulation have tended to benefit the OPS in value creation. It was also possible to conclude that the specialization of voluntary hospitals lead to better results in aggregating value. We have concluded that ANS norms affect the different categories of OPSs in several ways. It enhanced the relevance of considering the particularities of each category when performing any type of analysis. It is important to note that the higher level of regulation of ANS have tended to reduce the value added by regulated organizations. This context implied in a reduction of number of organizations on market and an increasing of the potential of formation of oligopolies, what face the public interest of the regulators entities.